Control strategies during fast turning manoeuvers - the free moment and its contribution to body rotation and joint loading - David, S.; Potthast, W. (Journal of Sports Sciences, 2021)
The purpose of this study was to identify the relationship between ACL relevant knee joint loading and the free (reaction) moment during 90° sidestepping task. It was hypothesized that the specific movement strategy of an athlete will impact this relationship and therefore contribute to joint loading. Functional principal component and canonical correlation analysis were used to understand the nature of free moments and their interaction with 3D joint loading in 52 athletes. It was observed that the orientation of either a positive or negative free moment is associated with different orientations and location of the foot segment at initial touch down. This impacted the rotational moment that is transferred to the knee joint: A higher internal reaction moment is observed when athletes were exposed to a positive free reaction moment, which potentially increases the load on the ACL. Furthermore, the free moment predicted joint moments and joint reaction forces. The interpretation of the principal components identified the function of the free moment to control body rotation. Free moments of different orientation were generated during the same movement, which highlights the importance of investigating individual movement strategies to understand potential injury risk and control factors.